Radiological and functional outcome of displaced mid-shaft clavicular fracture managed with open reduction and internal fixation with precountered anatomical clavicular locking plate: a prospective study - Panthi, Sagar; Shrestha, Rishiswor; Shakya, Rajan (International Journal of Research in Orthopaedics, 2020)
Background: Displaced mid-shaft clavicular fractures are treated by conservative methods which shows higher rate of malunion and non-union with suboptimal outcomes. Fracture fixation by pre-countered anatomical clavicular locking plate avoids these complications. This study aims to assess the radiological and functional outcome after open reduction and internal fixation by pre-countered anatomical clavicular locking plate. Methods: Fifty patients of mid-shaft clavicular fractures with age group of 18 to 60 years were treated with open reduction and internal fixation with precountered anatomical clavicular locking plate from, in the span of November 2018 to May 2020. All the patients were followed up for six months for the study. Final functional outcome was assessed in six months. Results: All the fractures united at the average time of 16.32±2.37 weeks. Mean Constant and Murley score was 96.0±5.20. The outcome was graded as excellent in 45 (90%), good in 4 (8%) and fair in 1 (2%) patients. Conclusions: Hence displaced mid-shaft clavicular fractures can be treated with by precountered anatomical clavicular locking plate.